The Personality of the Main Character in Tiana Amelia's Short Story Menantu Atau Pembantu: Sigmund Freud's Psychoanalysis Study - Nasution, Azhar; Nasution, Mutia (Politeknik Negeri Sriwijaya, 2024)
Research with the title